Compulsory Education Reform between the Profession and Policy in the Light of Justice and Equal Opportunities - Mojca Kovač Šebart; Damijan Štefanc; Tadej Vidmar (Center for Educational Policy Studies Journal)
Following the adoption of the conceptual design proposed by the White Paper in 1995 and the legislation adopted on this basis, the reform of primary school transformed its overall image. In the present paper, we discuss only some of the solutions and consider the events and changes that have occurred in the last twenty years, devoting special attention to the systemic, programme and process levels. At the systemic level, where the starting point was primarily to ensure justice and equal opportunities, we have managed to maintain an adequate public network and programme structure, despite various attempts to implement the solutions indicated in the White Paper of 2011, and notwithstanding interventions in the system that were not in fact always well thought out. Nonetheless, more attention should have been paid to reducing inequalities related to sociocultural circumstances and different regions in Slovenia. On the programme level, a consensus needs to be reached on what quality general education means to us; this would alleviate conflicting demands placed on teachers, students and planners of programme solutions. On the process level, however, we find that there is a lack of adequate professional support and systematic evaluation studies, as the quality of school cannot be judged solely on the basis of results from international research. In order to take a step forward on the process level, there is need for quality school-linked school policy that is based on various professions and aimed at raising quality rather than at self-promotion and budget cutting in the field of education.